Optimisation of metallic bismuth nanoparticle supported Pt-Bi(x%)/C hybrid electrocatalyst for cost effective and efficient hydrogen production in alkaline media - Dokhe, Revati; Ugale, Atul; Dube, Onkar; Varpe, Vaibhav; Galave, Chaitanya; Hattale, Gangadhar; Kadam, Rutuja; Virole, Vishal; Kumar, Ajay; Husale, Sudhir; Natu, Varun; Shevate, Rahul; et al. (International Journal of Hydrogen Energy, 2025)
The present study employed a simple mechanochemical method followed by 24-h ultrasonication to synthesize oxide-free metallic bismuth (Bi) nanoparticles. This was further used to synthesize a Pt-Bi(x%)/C (NC-x) hybrid electrocatalyst for the hydrogen evolution reaction in alkaline media. X-ray photoelectron spectroscopy and contact angle measurements reveal, Bi modifies the electronic structure and surface morphology of the Pt/C electrocatalyst, thus enhancing reaction kinetics and active site availability. The relative three-electrode study reveals that optimised NC-20 electrocatalyst reduces the overpotentials by 10.44 % and enhances the current density by 53 % compared to commercial Pt/C. The practical applicability of the NC-20 electrocatalyst was studied with the 13 cm2 single cell anion exchange membrane electrolyser. The catalyst demonstrates promising performance where the current density of NC-20//IrO2 relatively increases by 22.6 % compared to standard Pt/ C//IrO2, and shows continuous production and stable performance when monitored for 30 h.
Keywords: AEM; Bismuth nanoparticles; electrocatalyst; Full cell electrolysis; hydrogen evolution reaction; water electrolysis

Photoluminescence decay lifetime study of hydrothermally synthesized highly porous ruthenium-silica composite for optical dissolved oxygen sensing application - Hattale, Gangadhar; Kadam, Rutuja; Virole, Vishal; Pandya, Rinu; Paul, Aditya; Kumar, Ajay; Shevate, Rahul; Vanka, Kumar; Saha, Avishek; Kanawade, Rajesh (ACS Applied Nano Materials, 2026)
Pore size and surface area of photoluminescence (PL)-based transition metal composites play crucial roles in facilitating oxygen diffusion, thereby enhancing the response and sensitivity of optical dissolved oxygen (DO) sensors. In this study, we successfully applied the hydrothermal method to synthesize a porous ruthenium composite embedded in a silica matrix, demonstrating its effectiveness for optical DO sensing applications. The ruthenium-silica (Ru-Si) composites were synthesized using Ru(bpy)3 2+ and tetraethyl orthosilicate (TEOS) as precursors, with reaction temperatures ranging from 120 degrees C to 200 degrees C over a fixed duration of 4 h. The structural, morphological, and compositional characterization techniques confirmed the successful synthesis and evaluated the porosity, surface features, and chemical structure of the resulting composites. The optimized Ru-Si composite exhibited the highest porosity, characterized by a specific surface area of 996.78 m2 g- 1, and exhibited the highest decay lifetime of 8.14 mu s in deionized (DI) water, compared to other composites. Importantly, we demonstrate an excellent linear response of the synthesized Ru-Si composite to DO concentrations ranging from 2.58 to 11.16 mg L-1, with a Stern-Volmer constant of 0.12. Furthermore, a density functional theory study was conducted to investigate the electronic transitions and to elucidate the oxygen quenching mechanism of the excited Ru composite with molecular oxygen. The calculated photophysical parameters of the composite show good agreement with the experimental results. Preliminary results suggest that the synthesized Ru-Si with high pore size and surface area could be an efficient and effective composite for use in DO sensing applications.
Keywords: Hydrothermal method; opticalDO sensor; oxygen quenching; photoluminescent; ruthenium composite

Polysulfone-based polymer carbon dot membrane for optical dissolved oxygen sensing application - Kadam, Rutuja; Hattale, Gangadhar; Virole, Vishal; Pal, Sanjivani; Abraham, Athira; Paul, Aditya; Kumar, Ajay; Shevate, Rahul; Banpurkar, Arun; Kanawade, Rajesh; Saha, Avishek (Chemistry-An Asian Journal, 2026)
The precise monitoring of dissolved oxygen (DO) is essential across industrial, environmental, and biomedical applications. However, the state-of-the-art DO sensing methods often suffer from inherent limitations, which hinder their effectiveness for real-time and long-term DO monitoring. Optical DO sensing, despite its advantages, utilizes expensive metal complexes and is prone to photobleaching and slow response time. Here, we introduce a novel polymer carbon dot (PCD) as a promising candidate for lifetime-based optical DO sensing. The PCD is a metal-free, nontoxic, fluorescent, long decay-lifetime material that is synthesized through hydrothermal method. Our fluorescent PCD exhibits high emission quantum yield (24.32%), long decay-lifetime (10.43 & micro;s), and a linear response to DO concentrations ranging from 0.7 to 12.7 mg/L, with a Stern-Volmer constant of 0.1115. Further, to obtain better oxygen diffusion, high porosity, optical transparency, and high flexibility, PCD was embedded into a polysulfone matrix (PSF_PCD). The PSF_PCD membrane shows better results for the decay lifetime (9.4 & micro;s), surface energy (40.26 mN/m), and average pore diameter of 5 nm. Hence, the obtained results demonstrate the applicability of the PCD in optical DO sensors for real-time and long-term monitoring of DO levels.
Keywords: decay lifetime; dissolved oxygen; Hydrothermal method; polymer carbon dots; polysulfone-based membrane